Chitosan nanoparticles incorporate with curry leaf essential oil: Physicochemical characterization and in vitro release properties - R., Nur Fatin Nazurah; M.A., Noranizan; M.A.R., Nor-Khaizura; Z.A., Nur Hanani (Elsevier, 2024)
The use of essential oils as natural antioxidant, antimicrobial and insect repellent agent was limited by the loss of bioactive components especially volatile compounds. This study aimed to improve biological properties of curry leaf essential oil (CLEO) by producing nanometer sized particles through two different synthesis techniques; nanoencapsulation and nanoprecipitation. The methods produced different nanostructures; nanocapsules and nanospheres distinguished by the morphological structure (TEM analysis). Successful loading of CLEO into chitosan nanocarrier was proven by FTIR spectra. Zeta potential values for both nanostructures were more than +30 mV implying their stability against aggregation. CLEO loaded nanocapsules exhibited highest antibacterial properties against Gram-positive bacteria compared to nanospheres. Meanwhile, CLEO loaded nanospheres recorded up until 90.44 % DPPH radical scavenging properties, higher compared to nanocapsules. Both nanostructures demonstrated further improvement in antioxidant and antibacterial activities with the incorporation of higher chitosan concentration. In vitro release analysis indicated that CLEO undergo two-stage discharge mechanism where fast discharge occurred up until 12 h followed by sustained released afterwards. The two synthesis methods applied synergistically with greater chitosan concentration successfully produced nanostructures with >60 % encapsulation efficiency (EE). This concluded that both techniques were reliable to protect the bioactive constituents of CLEO for further used.